Respuesta :

Observation : No two such factors can be found !! 
Conclusion : Trinomial can not be factored

Equation at the end of step  2  :  6x2 - x - 4 = 0 ((2•3x2) - x) - 4 = 0 Step  2  :Trying to factor by splitting the middle term

 2.1     Factoring  6x2-x-4 

The first term is,  6x2  its coefficient is  6 .
The middle term is,  -x  its coefficient is  -1 .
The last term, "the constant", is  -4 

Step-1 : Multiply the coefficient of the first term by the constant   6 • -4 = -24 

Step-2 : Find two factors of  -24  whose sum equals the coefficient of the middle term, which is   -1 .

     -24   +   1   =   -23     -12   +   2   =   -10     -8   +   3   =   -5     -6   +   4   =   -2     -4   +   6   =   2     -3   +   8   =   5     -2   +   12   =   10     -1   +   24   =   23

Observation : No two such factors can be found !! 
Conclusion : Trinomial can not be factored

Equation at the end of step  2  : 6x2 - x - 4 = 0